Agreement Statistics Impacts of Prevalence Between the Two Clinicians in Binary Diagnostic Tests (Annals of Medical Research, 2021)
None
Keywords: Cohen’s Kappa Statistics; AC1 Statistics; Prevalance; Agreement Between Raters.